The length of the downstream exon and the substitution of specific sequences affect pre-mRNA splicing in vitro. - Furdon, P J (1988)
We have shown previously that truncation of the human beta-globin pre-mRNA in the second exon, 14 nucleotides downstream from the 3' splice site, leads to inhibition of splicing but not cleavage at the 5' splice site. We now show that several nonglobin sequences substituted at this site can restore splicing and that the efficiency of splicing depends on the length of the second (downstream) exon and not a specific sequence. Deletions in the first exon have no effect on the efficiency of in vitro splicing. Surprisingly, an intron fragment from the 5' region of the human or rabbit beta-globin intron 2, when placed 14 nucleotides downstream from the 3' splice site, inhibited all the steps in splicing beginning with cleavage at the 5' splice site. This result suggests that the intron 2 fragment carries a "poison" sequence that can inhibit the splicing of an upstream intron.